Characterisation And Pathogenicity Of Fungi Causing Sooty Blotch And Flyspeck (Sbfs) Disease Of Mango (Mangifera Indica L.) In Peninsular Malaysia - Tham, Khai Xin (2024)
The sooty blotch and flyspeck (SBFS) disease complex, caused by multiple fungal species, leads to black smudges and clusters of black spots on various fruits, including mango, impacting their marketability as fresh fruit. Although not previously reported in Malaysia, field visits in 2018 found similar SBFS disease symptoms on mango in various orchards in Perak. Therefore, this research aimed to: 1. Isolate and identify SBFS fungi on mango collected from Perak, Pahang, and Perlis based on morphological and molecular approaches; 2. Assess the phylogenetic relationship among the SBFS fungal isolates; 3. Determine the pathogenicity of the SBFS fungi isolated from mango. A total of 87 mango fruit showing SBFS disease symptoms were collected, and the number of SBFS colonies on each mango (CPM) and the percentage area of SBFS infection were determined. Subsequently, 2106 mango peel samples were obtained and subjected to isolation. Morphological characterization resulted in the identification of 33 pure cultures belonging to SBFS fungal genera, such as Zasmidum, Peltaster, Exophiala, Pseudocercospora, and Ochroconis. The DNA sequencing of the internal transcribed spacer (ITS) and large subunit (LSU) confirmed 18 representative isolates as distinct species, including Z. citrigriseum, Z. aporosae, Peltaster-like species, ‘Pseudopeltaster’, E. bergeri, E. spinifera, Pseudocercospora species, and O. cordanae. Phylogenetic analyses using maximum parsimony (MP) and maximum likelihood (ML) approaches indicated that the SBFS fungal complex on mango was related to both known SBFS members globally and non-SBFS taxa.